The impact of host's genetic susceptibility on Helicobacter pylori infection in children. Issue 30 (July 2017) - Mărginean, Maria Oana; Mărginean, Cristina Oana; Meliţ, Lorena Elena; Voidăzan, Septimiu; Moldovan, Valeriu; Bănescu, Claudia
Abstract : Abstract: The aim of our study was to investigate the impact of interleukin (IL)-6 190C/T, IL-6 174G/C, IL-6 572G/C, tumor necrosis factor-alpha (TNF-α) 308G/A, and angiotensin-converting enzyme (ACE) I/D gene polymorphisms on Helicobacter pylori ( H. pylori ) infection in children. A cross-sectional study was performed on 126 children (57 children with H. pylori infection and 69 children without H. pylori infection) aged between 3 and 18 years presenting to a Pediatrics Tertiary Hospital from Romania. Children were assessed clinically, endoscopically, histopathologically, and genetically. In our study, we found that the presence of the CT and CT+TT genotypes of IL-6 190C/T ( P  < .002 and P  = .04), allele G of IL-6 572 G/C polymorphism( P  = .01), genotypes GA and AA of TNF- α 308 G/A polymorphism ( P  = .04, P  = .01), and genotype II of ACE I/D polymorphism ( P  = .02) were associated with H. pylori infection, while the CC genotype of IL-6 174G/C polymorphism was scarcely encountered in children with H. pylori infection [ P  = .02, odds ratio (OR) = 0.06; 95% confidence interval (95% CI): 0.003–0.128]. Taking under consideration the 4 variant genotypes (IL-6 572G/C, IL-6 190C/T, TNF- α 308G/A, and ACE I/D ), we noticed a 2 times higher incidence of H. pylori infection (OR = 6.34; 95% CI: 2.15–25.8). We may consider that the IL-6 190C/T, IL-6 174G/C, IL-6 572G/C, TNF- α 308G/A, and ACE I/D gene polymorphisms may increase the children's susceptibility for acquiring H. pylori infection; therefore, they may contribute to the pathogenesis of H. pylori gastritis.